RT News, 4vii85ce - Rowan Tree Church (Minneapolis, MN: Rowan Tree Church, 1985)
The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. Considered by Rev. Beyerl to be neo-Alexandrian, the church has been based in Kirkland, Washington until October 2016 when they returned to Minnesota. The Church continues to maintain a community in Kirkland with many other communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, The Hermit’s Lantern, The Master Book of Herbalism, and A Wiccan Bardo, Revisited.
This newsletter was used as a mechanism to communicate internally with Church members. It provides a glimpse into the activities and the personalities involved within the church. Included are excerpts from letters, cassette tape recordings, and phone calls of members who are leaders or students progressing in the Mystery School, describing their feelings of their Initiations, sharing with members their life’s ordeals. Discussions on the Church’s administrative duties can also be found. The newsletter documents a very personal glimpse into the experiences of the body of people that make up an evolving Wiccan church.
Keywords: Rowan Tree Church--History; Periodicals; Wiccans--Communication; Rowan Tree Church--Finance; Church newsletters